Thoracic dorsal dermal sinus with secondarily infected intramedullary dermoid cyst - Patwari, Sriram; Reddy, Bhavana; Kapanigowda, Manoj; Ramesha, Sujith; Chadaga, Harsha (Asian Journal of Neurosurgery, 2019)
Dorsal dermal sinus (DDS) is an uncommon type of occult spinal dysraphism most often located in the lumbar region. Patients present either due to secondary infection or compression of neural structures by an associated dermoid or epidermoid cyst. We report a rare case of 2-year-old child who presented with progressive paraparesis with magnetic resonance imaging of spine showing a thoracic DDS with an infected intramedullary dermoid cyst. Partial excision of the dermoid cyst and resection of the sinus opening was done with partial clinical improvement postsurgery.
Keywords: Dermoid cyst; dorsal dermal sinus; intramedullary; secondary infection; thoracic region